PENGARUH EDUKASI AUDIO VISUAL TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG PEMERIKSAAN PAYUDARA SENDIRI - Maesitoh, Mila Suci; Widhiastuti, Ratna; Widyantoro, Wisnu (Universitas Pesantren Tinggi Darul Ulum, 2024)
Breast self-examination (SADARI) is one of the first ways to find out breast cancer by seeing and feeling if there are abnormalities. The Indonesian Ministry of Health in 2022 said that the incidence of breast cancer in Indonesia was 26 per 100 thousand population and 70% were detected at an advanced stage and could result in death. The delay in early detection of breast cancer is due to lack of knowledge and information as well as attitudes that tend to be indifferent and do not care about breast health. Health education about SADARI is important as an effort to prevent the incidence of breast cancer. The purpose of this study was to determine the effect of providing education on the knowledge and attitudes of adolescent girls about breast self-examination at SMP N 1 Moga. This type of research is a quantitative using a pre-posttest design. The population in this study was 9th grade female students who were taken using total sampling of 141 respondents. The statistical test of the Wilcoxcon signed rank test showed a p value of 0.000 <0.05, which means that there is an effect of providing education on the knowledge and attitudes of female students through audio visual media. Based on this research, it is hoped that female students can apply knowledge and show a positive attitude in the application of SADARI as an effort to detect breast cancer early. Keyword: SADARI; education; breast cancer; knowledge and attitude.